Can Concerns for Social Status Mitigate the 'Lemons Problem'? Experimental Evidence from the Indian Caste Hierarchy. (August 2019) - Dugar, Subhasish; Bhattacharya, Haimanti
We conducted a lab-in-the-field experiment to analyse if and how information about an individual's social status influences efficient choices in a two-party hidden information game in which trust and trustworthiness play a central role. Recruitment of subjects from three status groups based on the Indian caste system allows us to distinguish between identity-based and status-based preferences. We find that all status groups exhibit strong in-group favouritism which fosters efficiency. The decisions of subjects from the two lower-status groups align well with identity-based preferences as they treat their out-group co-players in a statistically equivalent manner. However, subjects from the top of the hierarchy exhibit behaviour consistent with status-based preferences as their propensity to choose efficient actions systematically declines with an increase in the distance between their status and their co-player's status. Thus, the behaviour of the top-status group closely conforms to the actual social rankings of these caste groups in India, whereas the behaviour of lower-status groups displays a binary classification of people into 'us' and 'them'.